Confronting a Compound Crisis: The School Principal’s Role During Initial Phase of the COVID-19 Pandemic - Reyes-Guerra, Daniel; Maslin-Ostrowski, Patricia; Barakat, Maysaa Y.; Stefanovic, Melanie Ann (Frontiers in Education, 2021)
The COVID-19 pandemic brings to the forefront and catalyzes long-unconfronted racial and economic inequities, in addition to economic collapse and deep political divisions, which impact students and schools. This resulted in a compound crisis requiring a novel conceptualization of school leadership during times of crisis. Our qualitative study captures the leadership experience of principals during the global crisis - the COVID-19 pandemic - beginning from when schools were closing in March 2020 to the end of the school year in June. Crisis leadership, transformative leadership and social capital constitute the overarching conceptual framework for this study. The purpose of this case study was to discover how principals engaged in their thinking and practice to handle the compound crisis, in order to generate a rich description and gain an understanding of school leadership during the first phase of the COVID-19 pandemic. Research questions were: What were the challenges and complications of leading during the initial phase of the compound crisis from the perspective of principals? How did principals respond? What were the leadership practices that emerged? This study used a purposeful, maximum variation sample of nine principals in Florida. We sought balance in gender, race and ethnicity, and grade level. In-depth interviews were conducted using a structured protocol. Analysis treated each principal as an individual case, then cross-case thematic analysis was employed to uncover common patterns and themes. There are three key findings. Participants draw upon their individual reservoirs of shared leader qualities, including personalized and pragmatic communication; they lead with flexibility, creativity and care; they bend rules and shift priorities; and show resilience under pressure. Principals also tap into their schools’ strengths, including school contexts and in-house expertise. Finally, they create and leverage inter-school connections. The first phase of the crisis pushed principals to prioritize care, safety, and wellbeing of students, teachers, and communities above accountability measures and systemic institutional constraints. A need to examine or re-examine existing systemic inequities and a call to action for equity is the next logical step. This is echoed by principals, who expressed that going back to old ways is no longer an option.